Socio-economy, lifestyle, nutritional status, biochemical parameters and blood pressure associated with cardiovascular disease risk markers among Malay employees in Universiti Putra Malaysia - Abd. Azimi, Norshafawati (2013)
Cardiovascular disease (CVD) has become the major health problem in the developed and developing countries. The objective of this cross-sectional study was to determine the associations between socio-economic status, lifestyle factors, nutritional status, biochemical parameters and blood pressure with CVD risk markers among Malay academic and non-academic staff aged 30-55 years-old at Universiti Putra Malaysia (UPM). Data collection was carried out from October 2011 until January 2012. All subjects were systematically selected by using a sampling frame from a name list obtained from the registrar office. Subjects who were pregnant, lactating, on study or long medical leave, having fever, cough or cold, injury, and on medication, except for hypertension, diabetes and hyperlipidemia during data collection were excluded from this study. A set of questionnaire was used to determine socio-demographic information, medical and family history, tobacco use, physical activity, scale of depression, anxiety and stress, and dietary intake. Anthropometric measurements were conducted by measuring body weight, height, waist and hip circumference and blood pressure (BP).A 10ml of fasting blood was collected to determine levels of homocysteine, C-reactive protein (CRP), blood glucose, and lipid profiles of the subjects. Data were analysed by using SPSS version 19.0. A total of 122 subjects (40.2% male, 59.8% female, response rate of 97.6%) agreed to participate in this study with mean age of 41.93 ± 8.26 years-old. More than half of the subjects had household income more than RM4000. Only 12.3% of the subjects were current smokers and majority never smoked. About 32% of the subjects were passive smokers. Majority of the subjects had high physical activity level, normal score for depression, anxiety, stress and were overweight. Almost half of the subjects were at high risk waist circumference (WC) while only a few of them were at high risk waisthip ratio (WHR). Foods and drinks that were highly consumed by the subjects were plain water, cooked rice, green leafy vegetables, sugar, marine fish, and tea. Majority of the subjects were categorized as prehypertensive for systolic BP and normal for diastolic BP. Majority of them had borderline levels for total cholesterol (TC), near or above optimal levels for low density lipoprotein (LDL), high levels of high density lipoprotein (HDL), normal levels of triglyceride (TG), at low risk of TC:HDL ratio, and normal fasting blood glucose. Almost 38% of them were at average risk of high sensitivity (hs) CRP and majority of them had moderately high levels of homocysteine.Bivariate analysis showed that log hs-CRP were associated with age, anxiety, WC, systolic BP, diastolic BP, BMI, TC, TG, LDL, TC: HDL ratio, and log fasting blood glucose. In addition, there were associations between homocysteine with sex, not a passive smoker, WC, diastolic BP, WHR, TC, TG, and TC:HDL ratio. Multivariate analysis revealed that BMI was the strongest factor in predicting the level of log hs-CRP while sex (female) and TG was the strongest factor in predicting homocysteine level. Thus, this study suggests that sex (female), BMI and TG level have an important role in the development of CVD event among Malay employees in a higher learning institution.